Predictors of University Adaptation and Grades for Direct Entry and Transfer Students - Quinn-Nilas, Christopher; Kennett, Deborah J.; Maki, Karen (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
This study compared the differences between students entering university directly from high school vs. those transferring from other higher education institutions for the variables of the academic self-control model (general resourcefulness, academic resourcefulness, academic self-efficacy, preparedness, failure attributions, and university adaptation). The goals of the research were to test the following: (1) the full academic self-control model using a large sample of undergraduate students to predict university adaptation and final grades; (2) if the pathways of association implied by the model are equally predictive regardless of whether students are direct entry, university transfer, or college transfer; and (3) if the means of the variables differed among these three groups. Results replicated previous studies showing that, for the entire sample, general resourcefulness, preparedness, explanatory style for failure, and academic self-efficacy were strongly predictive of academic resourcefulness, which, in turn, was strongly associated with university adaptation and grade. Moreover, the indirect and direct pathways of the model were found to be equivalent for the three student groups. Comparisons of the groups’ means for the psychological variables revealed the university transfer group to have the most favourable scores followed by the college transfer group. The findings suggest that both college and university transfer students bring valuable skills to undergraduate programs and the keys to their university adaptation and academic achievement are the same as for direct entry students.